2022
DOI: 10.1038/s41467-022-35399-8
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the transiently populated closed-state of human HSP90 ATP binding domain

Abstract: HSP90 are abundant molecular chaperones, assisting the folding of several hundred client proteins, including substrates involved in tumor growth or neurodegenerative diseases. A complex set of large ATP-driven structural changes occurs during HSP90 functional cycle. However, the existence of such structural rearrangements in apo HSP90 has remained unclear. Here, we identify a metastable excited state in the isolated human HSP90α ATP binding domain. We use solution NMR and mutagenesis to characterize structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…This suggests that residues 104–114 of the ATP-lid in apo N-HSP90α exist in different loop conformations in solution. The binding of specific ligands, different crystallization conditions, additives, pH, and other factors can alter the pre-existing conformational equilibrium. , This leads to a shift in the population distribution toward more stable conformations, thereby increasing the proportion of this conformation. In the isolated structure of N-HSP90α, Henot et al also observed a “closed” conformation of the ATP-lid, with an occupancy of 3–4% at room temperature .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that residues 104–114 of the ATP-lid in apo N-HSP90α exist in different loop conformations in solution. The binding of specific ligands, different crystallization conditions, additives, pH, and other factors can alter the pre-existing conformational equilibrium. , This leads to a shift in the population distribution toward more stable conformations, thereby increasing the proportion of this conformation. In the isolated structure of N-HSP90α, Henot et al also observed a “closed” conformation of the ATP-lid, with an occupancy of 3–4% at room temperature .…”
Section: Resultsmentioning
confidence: 99%
“…The binding of specific ligands, different crystallization conditions, additives, pH, and other factors can alter the pre-existing conformational equilibrium. , This leads to a shift in the population distribution toward more stable conformations, thereby increasing the proportion of this conformation. In the isolated structure of N-HSP90α, Henot et al also observed a “closed” conformation of the ATP-lid, with an occupancy of 3–4% at room temperature . However, this helical conformation remains elusive in the absence of ligand binding, likely triggered by specific binding events.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations